The parental challenge: knowledge, attitudes, and practices on iron deficiency anemia in Tabuk - Sawsan Mohammed Alblewi; Amerah M Alatawi; Faisal Mayudh Althobaiti; Adel Ali Alharfi; Faisal Mohammed Alamrani; Yazeed Mahmoud Ajwah; Omar Muslih Albalawi; Mohammed Majed Alquayr; Ariam Ebraheem Alshammari (Italian Journal of Medicine, 2025)
Iron deficiency anemia (IDA) is common in children worldwide and has been recognized as a major challenge to the health of children and society. Adequate knowledge of IDA is necessary for effective prevention and treatment. This study aimed to assess parental awareness of IDA and to identify factors that influence their level of knowledge. This cross-sectional survey study was carried out in Tabuk City, Saudi Arabia. The study enrolled 403 parents aged 18 years or older. A link to the electronic survey was sent via social media platforms to collect data. Descriptive and inferential statistics were performed. Most participants were female and aged 36 years or older (72.5% and 75.2%, respectively). The level of parental knowledge regarding IDA varied between good (60.0%), moderate (29.0%), and poor (11.0%). Multivariable binary logistic regression revealed that young parents aged 18-25 had more than threefold increased odds [adjusted odds ratio (AOR): 3.475] of having a low to moderate level of knowledge. In addition, males were more significantly associated with an increased risk of low knowledge compared to females (AOR: 1.945). Parents with less than a university education were more than twice as likely to have poor to moderate knowledge (AOR: 2.157). According to the study's findings, 60% of parents in Tabuk City, Saudi Arabia, were well-informed about all aspects of IDA. The two main areas with the least amount of knowledge were signs and symptoms and understanding the meaning of anemia. Young parents (18-25 years old), men, and parents with less than a university degree are risk factors associated with a higher likelihood of low knowledge.